REFINEMENT OF INDICATORS AND DEVELOPMENT OF ALGORITHMS TO DETECT SINGS OF DELIBERATE BANKRUPTCY - Andrei A. Byrbytkin (Статистика и экономика, 2016)
The article proposes to consider clarifyingadditions to the methodology of ﬁnancial analysis liquidator affaires «On Insolvency(Bankruptcy)», as well as detection ofdeliberate bankruptcy on transport enterprises.